Outline of a monetary approach to the theory of tax incidence - PARRAVICINI, G. (PSL Quarterly Review, 2014)
The present paper deals with the relationship between taxation and prices, and in particular is concerned with the question of money transfers and price changes due to various kinds of taxes in conditions of a general monetary constraint. An attempt is made at discovering whether it is possible for prices to change irrespective of changes in the quantity of money and in its velocity of circulation, and whether price changes are or are not the same in the case of a direct tax on income, and in the case of an indirect tax on goods. The analysis leads to an examination of the validity of H.G. Brown’s analysis, which was later developed by E.R. Rolph. Both authors reached the conclusion that direct taxes on income and indirect taxes on goods have the same effect, both as regards prices, which remain unchanged in either case, and as regards incidence. JEL: H20, H21, E51, B31